Integrating academic analytics for supporting accreditation and international cooperation: TEC and UABCS experience - Chacón-Rivas, Mario; Francesa-Alfaro, Agustín; Carreño-León, Mónica; Sandoval-Bringas, Andrés (IEEE, 2017)
Information is the most important asset of organizations, currently, the fast, effective and accurate access is vital for strategic decision making and the organizations competitiveness. The education area is not the exception, so this article aims to share the experiences of collaboration between two Universities about learning analitycs and academic analytics tools, to motivate other universities to generate collaboration links. In this article, we refer the differences between learning analytics and academic analytics, the description of some tools developed at the Instituto Tecnologico de Costa Rica and ´ the Universidad Autonoma de Baja California Sur, focused ´ on these topics and the experiences of collaboration between both universities in two ways: sharing the current tools and how to develop new tools, capable of integrating with the infrastructure of each university in particular.
© © 2017 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.
Keywords: Educación; Competitividad; Herramientas; Software; Toma de decisiones; Organización; Instituciones de educación superior